Medical vision: web and mobile medical image retrieval system based on google cloud vision - I Ketut Gede Darma Putra; Dewa Made Sri Asra; I Gusti Ngurah Dwiva Hardijaya; I Gede Galang Surya Prabawa; I Made Aris Satia Widiatmika (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The application of information technology is rapidly utilized in the medical system. There is also a massive development in the automatic method for recognizing and detecting objects in the real world. In this study, we present a system called Medical Vision which is designed for people who has no expertise in medical. Medical Vision is a web and mobile-based application to give an initial knowledge in a medical image. This system has 5 features; object detection, web detection, object labeling, safe search, and image properties. These features are run by embedding Google Vision API in the system. We evaluate this system by observing the result of some medical images which inputted into the system. The results showed that our system presents a promising performance and able to give relevant information related to the given image.